Perfect shadow - Weeks, Brent (Orbit, 2017)
Gaelan Starfire is a farmer, happy to be a husband and a father; a careful, quiet, simple man. He's also an immortal, peerless in the arts of war. Over the centuries, he's worn many faces to hide his gift, but he is a man ill-fit for obscurity, and all too often he's become a hero, his very names passing into legend: Acaelus Thorne, Yric the Black, Hrothan Steelbender, Tal Drakkan, Rebus Nimble. But when Gaelan must take a job hunting down the world's finest assassins for the beautiful courtesan-and-crimelord Gwinvere Kirena, what he finds may destroy everything he's ever believed in.